diff --git a/Bookshelf/Enderton/Logic.tex b/Bookshelf/Enderton/Logic.tex index 1bf97aa..8f1862c 100644 --- a/Bookshelf/Enderton/Logic.tex +++ b/Bookshelf/Enderton/Logic.tex @@ -5,6 +5,12 @@ \externaldocument[S:]{Set} +% Truth table start and final color +\definecolor{TTStart}{gray}{0.95} +\definecolor{TTEnd}{rgb}{1,1,0} +\newcolumntype{s}{>{\columncolor{TTStart}}c} +\newcolumntype{e}{>{\columncolor{TTEnd}}c} + \begin{document} \header{A Mathematical Introduction to Logic}{Herbert B. Enderton} @@ -796,32 +802,64 @@ \end{proof} -\subsection{\sorry{Exercise 1.2.1}}% +\subsection{\verified{Exercise 1.2.1}}% \hyperlabel{sub:exercise-1.2.1} Show that neither of the following two formulas tautologically implies the other: - \begin{gather*} - (A \Leftrightarrow (B \Leftrightarrow C)), \\ + \begin{gather} + (A \Leftrightarrow (B \Leftrightarrow C)), + \hyperlabel{sub:exercise-1.2.1-eq1} \\ ((A \land (B \land C)) \lor ((\neg A) \land ((\neg B) \land (\neg C)))). - \end{gather*} + \hyperlabel{sub:exercise-1.2.1-eq2} + \end{gather} \textit{Suggestion}: Only two \nameref{ref:truth-assignment}s are needed, not eight. + \code*{Enderton.Logic.Chapter\_1} + {Enderton.Logic.Chapter\_1.exercise\_1\_2\_1\_i} + + \code{Enderton.Logic.Chapter\_1} + {Enderton.Logic.Chapter\_1.exercise\_1\_2\_1\_ii} + \begin{proof} - TODO + First, suppose $A = T$, $B = F$, and $C = F$. + Then \eqref{sub:exercise-1.2.1-eq1} evaluates to $T$ but + \eqref{sub:exercise-1.2.1-eq2} evaluates to $F$. + Therefore $\eqref{sub:exercise-1.2.1-eq1} \not\vDash + \eqref{sub:exercise-1.2.1-eq2}$. + + Next, suppose $A = F$, $B = F$, and $C = F$. + Then \eqref{sub:exercise-1.2.1-eq2} evaluates to $T$ but + \eqref{sub:exercise-1.2.1-eq1} evaluates to $F$. + Therefore $\eqref{sub:exercise-1.2.1-eq2} \not\vDash + \eqref{sub:exercise-1.2.1-eq1}$. \end{proof} -\subsection{\sorry{Exercise 1.2.2a}}% +\subsection{\verified{Exercise 1.2.2a}}% \hyperlabel{sub:exercise-1.2.2a} Is $(((P \Rightarrow Q) \Rightarrow P) \Rightarrow P)$ a tautology? + \code*{Enderton.Logic.Chapter\_1} + {Enderton.Logic.Chapter\_1.exercise\_1\_2\_2a} + \begin{proof} - TODO + Yes. + To prove, consider the following truth table: + $$ + \begin{array}{s|c|s|c|s|e|s} + (((P & \Rightarrow & Q) & \Rightarrow & P) & \Rightarrow & P) \\ + \hline + T & T & T & T & T & T & T \\ + T & F & F & T & T & T & T \\ + F & T & T & F & F & T & F \\ + F & T & F & F & F & T & F + \end{array} + $$ \end{proof} -\subsection{\sorry{Exercise 1.2.2b}}% +\subsection{\pending{Exercise 1.2.2b}}% \hyperlabel{sub:exercise-1.2.2b} Define $\sigma_k$ recursively as follows: $\sigma_0 = (P \Rightarrow Q)$ and @@ -829,7 +867,95 @@ $\sigma_k$ a tautology? (Part (a) corresponds to $k = 2$.) \begin{proof} - TODO + + We prove that $\sigma_k$ is a tautology if and only if $k$ is an even + integer greater than zero. + To do so, we show (i) that $\sigma_k$ is a tautology for all even $k > 0$, + (ii) $\sigma_0$ is not a tautology, and (iii) $\sigma_k$ is not a + tautology for all odd $k$. + + \paragraph{(i)}% + \hyperlabel{par:exercise-1.2.2b-i} + + Let $P(k)$ be the predicate, "$\sigma_k$ is a tautology." + We prove $P(k)$ holds true for all even $k > 0$ via induction. + + \subparagraph{Base Case}% + + Let $k = 2$. + By definition, + $$\sigma_2 = (((P \Rightarrow Q) \Rightarrow P) \Rightarrow P).$$ + \nameref{sub:exercise-1.2.2a} indicates $\sigma_2$ is a tautology. + Hence $P(2)$ is true. + + \subparagraph{Inductive Step}% + + Suppose $P(k)$ holds for some even $k > 0$. + By definition, + $$\sigma_{k + 2} = ((\sigma_{k} \Rightarrow P) \Rightarrow P).$$ + Consider the truth table of the above: + $$ + \begin{array}{c|c|s|e|s} + ((\sigma_k & \Rightarrow & P) & \Rightarrow & P) \\ + \hline + T & T & T & T & T \\ + T & T & T & T & T \\ + T & F & F & T & F \\ + T & F & F & T & F + \end{array} + $$ + This shows $\sigma_{k+2}$ is a tautology. + Hence $P(k + 2)$ is true. + + \subparagraph{Subconclusion}% + + By induction, $P(k)$ is true for all even $k > 0$. + + \paragraph{(ii)}% + + By definition, $$\sigma_0 = (P \Rightarrow Q).$$ + This is clearly not a tautology since $\sigma_0$ evaluates to $F$ when + $P = T$ and $Q = F$. + + \paragraph{(iii)}% + + Let $k > 0$ be an odd natural number. + There are two cases to consider: + + \subparagraph{Case 1}% + + Suppose $k = 1$. + Then $\sigma_k = \sigma_1 = ((P \Rightarrow Q) \Rightarrow P)$. + The following truth table shows $\sigma_1$ is not a tautology: + $$ + \begin{array}{s|c|s|e|s} + (((P & \Rightarrow & Q) & \Rightarrow & P) \\ + \hline + T & T & T & T & T \\ + T & F & F & T & T \\ + F & T & T & F & F \\ + F & T & F & F & F + \end{array} + $$ + + \subparagraph{Case 2}% + + Suppose $k > 1$. + Then $k - 1 > 0$ is an even number. + By definition, $$\sigma_k = (\sigma_{k-1} \Rightarrow P).$$ + By \eqref{par:exercise-1.2.2b-i}, $\sigma_{k-1}$ is a tautology. + The following truth table shows $\sigma_k$ is not: + $$ + \begin{array}{c|e|s} + (\sigma_{k-1} & \Rightarrow & P) \\ + \hline + T & T & T \\ + T & T & T \\ + T & F & F \\ + T & F & F + \end{array} + $$ + \end{proof} \subsection{\sorry{Exercise 1.2.3a}}% diff --git a/Bookshelf/Enderton/Logic/Chapter_1.lean b/Bookshelf/Enderton/Logic/Chapter_1.lean index 2614e4b..92e87ed 100644 --- a/Bookshelf/Enderton/Logic/Chapter_1.lean +++ b/Bookshelf/Enderton/Logic/Chapter_1.lean @@ -390,4 +390,68 @@ theorem exercise_1_1_5_b (α : Wff) (hα : ¬α.hasNotSymbol) ] exact inv_lt_one (by norm_num) +/-! #### Exercise 1.2.1 + +Show that neither of the following two formulas tautologically implies the +other: +``` +(A ↔ (B ↔ C)) +((A ∧ (B ∧ C)) ∨ ((¬ A) ∧ ((¬ B) ∧ (¬ C)))). +``` +*Suggestion*: Only two truth assignments are needed, not eight. +-/ +section Exercise_1_2_1 + +private def f₁ (A B C : Prop) : Prop := + A ↔ (B ↔ C) + +private def f₂ (A B C : Prop) : Prop := + ((A ∧ (B ∧ C)) ∨ ((¬ A) ∧ ((¬ B) ∧ (¬ C)))) + +theorem exercise_1_2_1_i + : f₁ True False False ≠ f₂ True False False := by + unfold f₁ f₂ + simp + +theorem exercise_1_2_1_ii + : f₁ False False False ≠ f₂ False False False := by + unfold f₁ f₂ + simp + +end Exercise_1_2_1 + +section Exercise_1_2_2 + +/-- #### Exercise 1.2.2a + +Is `(((P → Q) → P) → P)` a tautology? +-/ +theorem exercise_1_2_2a (P Q : Prop) + : (((P → Q) → P) → P) := by + tauto + +/-! #### Exercise 1.2.2b + +Define `σₖ` recursively as follows: `σ₀ = (P → Q)` and `σₖ₊₁ = (σₖ → P)`. For +which values of `k` is `σₖ` a tautology? (Part (a) corresponds to `k = 2`.) +-/ + +private def σ (P Q : Prop) : ℕ → Prop + | 0 => P → Q + | n + 1 => σ P Q n → P + +theorem exercise_1_2_2b_i (k : ℕ) (h : Even k ∧ k > 0) + : σ P Q k := by + sorry + +theorem exercise_1_2_2b_ii + : ¬ σ True False 0 := by + sorry + +theorem exercise_1_2_2b_iii (n : ℕ) (h : Odd n) + : ¬ σ False Q n := by + sorry + +end Exercise_1_2_2 + end Enderton.Logic.Chapter_1 diff --git a/Bookshelf/Enderton/Set.tex b/Bookshelf/Enderton/Set.tex index e95adf8..c279881 100644 --- a/Bookshelf/Enderton/Set.tex +++ b/Bookshelf/Enderton/Set.tex @@ -6,6 +6,8 @@ \input{../../preamble} \makecode{../..} +\externaldocument[S:]{../../Common/Real/Sequence} + \newcommand{\ineq}{\,\mathop{\underline{\in}}\,} \begin{document} @@ -854,7 +856,7 @@ Therefore $V_1 = A \cup \powerset{V_0}$. This proves $P(1)$ holds true. - \paragraph{Induction Step}% + \paragraph{Inductive Step}% Suppose $P(n)$ holds true for some $n \geq 1$. Consider $V_{n+1}$. @@ -8611,7 +8613,7 @@ TODO \end{proof} -\subsection{\sorry{Exercise 6.2}}% +\subsection{\unverified{Exercise 6.2}}% \hyperlabel{sub:exercise-6-2} Show that in Fig. 32 we have: @@ -8622,7 +8624,32 @@ \end{align*} \begin{proof} - TODO + \begin{figure}[ht] + \label{sub:exercise-6-2-fig1} + \includegraphics[width=0.6\textwidth]{fig-32} + \centering + \end{figure} + Let $m, n \in \omega$. + We note the next point following $(m, n)$ that coincides with the $x$-axis + is $(m + n, 0)$. + We can then formulate the sum of points seen as + \begin{equation} + \hyperlabel{sub:exercise-5-2-eq1} + \left[ \sum_{i=0}^{m + n} (i + 1) \right] - n. + \end{equation} + All that remains is showing \eqref{sub:exercise-5-2-eq1} identifies with + the equation for $J$. + \eqref{sub:exercise-5-2-eq1} is an arithmetic series. + By \nameref{S:sub:sum-arithmetic-series}, + \begin{align*} + \left[ \sum_{i=0}^{m + n} (i + 1) \right] - n + & = \frac{[(m + n) + 1][1 + (m + n + 1)]}{2} - n \\ + & = \frac{[(m + n) + 1][(m + n) + 2]}{2} - n \\ + & = \frac{(m + n)^2 + 2(m + n) + (m + n) - 2n}{2} \\ + & = \frac{1}{2}[(m + n)^2 + 3m + n] \\ + & = J(m, n). + \end{align*} + Hence $J$ is correctly defined. \end{proof} \subsection{\sorry{Exercise 6.3}}% diff --git a/Bookshelf/Enderton/Set/images/fig-32.png b/Bookshelf/Enderton/Set/images/fig-32.png new file mode 100644 index 0000000..d0724ed Binary files /dev/null and b/Bookshelf/Enderton/Set/images/fig-32.png differ diff --git a/preamble.tex b/preamble.tex index 249ba19..18c67ac 100644 --- a/preamble.tex +++ b/preamble.tex @@ -1,5 +1,6 @@ \usepackage{amsfonts, amsmath, amssymb, amsthm} \usepackage{bigfoot} +\usepackage{colortbl} \usepackage{comment} \usepackage[shortlabels]{enumitem} \usepackage{etoolbox}